(untitled) (Wudil Journal of Science and Technology Education, 2025)
The experiment was conducted at the Federal University of Technology Owerri Research farm between the end of May – the end September of 2024, with the aim of assessing some local and improved sweet potato varieties for growth and yield potential. Each variety was planted in a 3m × 3m (9m2) plot size, at a planting distance of 1.0m ×0.3m. The experiment was laid out in Randomized Complete Block Design with three replications and separated from each other at a space of 1m. Vine cuttings were planted on ridges and poultry manure was applied at four weeks after plantingat the rate of 3.2t/ha. Data for growth and yield parameters were collected and subjected to Analysis of variance and means separation was done using Least Significant Difference (LSD). The Analysis of Variance showed Significant differences (p<0.05) among the sweet potato varieties for both growth and yield parameters. Solo Gold recorded the highest mean percentage sprout count emergence of 88.88% followed by Ex-Igbariam (81.48%), while the lowest was obtained in SokuwaDuglu(1.85%).Mothers Delight had the highest total yield with 81.30kg/ha which was followed by Bende 2 (72.55kg/ha) and Bota Akpulu (45.65kg/ha) respectively. The lowest yield was obtained from SokuwaDuglu (0.63kg/ha).The various agronomic parameters assessed which showed significant differences were ranked (rank 1- 15).Bende 2 with Rank Summation Index (RSI) value (34) was the best performing variety, followed by TIS 8164 and mothers delight with RSI 62 and 65 respectively. On the other hand, the RSI showed the worst performing variety insokuwuduglu with RSI (151), Apiduglu and TIS 87/0087 with RSI 122 and 97 respectively. Therefore, to boost the harvest of sweet potato in this region, the varieties Bende 2 and Mothers delight are highly recommended.